Cyberstalking on Social Media, How Does Islam View It? - Nurul Isnaini; Annisa Azzahro (IQTIDA : Journal of Da'wah and Communication, 2023)
With the development of information technology and the internet, social media has replaced real social relations with virtual ones. However, virtual social relations carry risks, one of which is Cyberstalking (Rohman & Sugeng 2022) Cyberstalking is a dangerous cybercrime and targets many people, communities, and organizations (Baer, 2020) As a crime, cyberstalking fulfills the elements of a criminal act which results in disruption of social order (Wall, 2007). Thus, cyberstalking is contrary to Islamic principles because it creates an insecure atmosphere. This research is library research using library materials in the form of books, journals, magazines, and other library sources as study material (Sukmadinata, 2010). Researchers will use a descriptive qualitative approach. Cyberstalking is a term used to describe various behaviors that involve repeated threats and/or harassment using electronic mail or other computer-based communications that will make people afraid or concerned for their safety (Gopalan, R.T. 2020). In Islam, these actions are prohibited acts because they contain elements of harassment, threats, harassment, or coercion. In interacting, Islam puts forward the concept of "rahmatan lil alamin" which means being a source of mercy and benefit for all creation (Rouzi, K.S., Suud, F.M., & Chaer, M.T. 2021), emphasizing values such as tolerance, discipline, social care, responsibility answer, and love peace (Nasir, M.S., & Khalilurrahman 2022). These values can be applied to the concept of privacy, encouraging individuals to respect the boundaries and personal space of others. The Qur'an teaches that stalking and harassment are prohibited by Allah, and humans need to be careful when engaging in such activities. In conclusion, cyberstalking is a form of harassment that violates Islamic principles and can cause harm to individuals and society.